2017
DOI: 10.1080/02602938.2017.1356906
|View full text |Cite
|
Sign up to set email alerts
|

Using technology to facilitate effective assessment for learning and feedback in higher education

Abstract: The aims of this paper are to examine and critically evaluate a selection of different technological methods that was specifically chosen for the alignment with, and potential to enhance extant assessment for learning practice. The underpinning perspectives are that (a) both formative and summative assessment are valuable opportunities for learning and (b) using technology may enhance learning in assessment and feedback processes. Drawing on the literature and empirical evidence from a research study in a Scot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 34 publications
4
63
1
8
Order By: Relevance
“…Despite a growing number of studies into technological adoption within teaching and learning in higher education (Habib & Johannesen, ; King & Boyatt, ; Paiva, Morais, Costa, & Pinheiro, ) there is a need for studies that explicitly consider technology and assessment utilisation of academic staff (Bennett et al , ; Deeley, ). Studies which focus on student’s perspectives of technology and assessment prevail including a critical emphasis on the student voice within digital technology use (Manca, Grion, Armellini, & Devecchi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing number of studies into technological adoption within teaching and learning in higher education (Habib & Johannesen, ; King & Boyatt, ; Paiva, Morais, Costa, & Pinheiro, ) there is a need for studies that explicitly consider technology and assessment utilisation of academic staff (Bennett et al , ; Deeley, ). Studies which focus on student’s perspectives of technology and assessment prevail including a critical emphasis on the student voice within digital technology use (Manca, Grion, Armellini, & Devecchi, ).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of student thinking in summative tasks was enhanced, and a positive culture of peer support and collaboration was built from early in the semester. Students were able to give fast feedback to themselves about how new ideas related to their professional practice early in the semester and have those impressions confirmed by lecturers and peers, so they felt on the right track (Deeley, 2018). They were also able to monitor their own progress of ideas and engage in deeper reflection, a desired feedback goal (Boud & Molloy, 2013).…”
Section: Discussion: Sociotechnical Insights About Designing For Fastmentioning
confidence: 99%
“…Feedback technologies that enable this near-instant feedback are diverse, including technologies such as online quizzes and in-class polling (Han & Finkelstein, 2013) as well as more complex game-based learning (Holbrey, 2020), clinical simulations (Bernaitis et al, 2018) and automated writing feedback (Shibani et al, 2017). Rapid feedback technologies can help learners to feel they are on the right track (Deeley, 2018), but feedback focused on predetermined responses may be of limited value for deep learning (Winstone & Carless, 2020) or for transfer between assessment tasks (Hill & West, 2020). This research aimed to investigate technology that could lead to feedback that was open, dialogic and ultimately faster for students and for teachers to inform ongoing learning.…”
Section: Digital Technologies Enabling and Automating Faster Feedbackmentioning
confidence: 99%
“…There is ample evidence in the literature to support the use of assessment for learning in higher education (Deeley 2017). Studies have reported higher learning and retention through reassessing content instead of revisiting it (Augustin 2014).…”
Section: Discussionmentioning
confidence: 99%